2016
DOI: 10.1371/journal.pone.0165047
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus Broadly Neutralizing Monoclonal Antibodies Isolated 25 Years after Spontaneous Clearance

Abstract: Hepatitis C virus (HCV) is world-wide a major cause of liver related morbidity and mortality. No vaccine is available to prevent HCV infection. To design an effective vaccine, understanding immunity against HCV is necessary. The memory B cell repertoire was characterized from an intravenous drug user who spontaneously cleared HCV infection 25 years ago. CD27+IgG+ memory B cells were immortalized using BCL6 and Bcl-xL. These immortalized B cells were used to study antibody-mediated immunity against the HCV E1E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 50 publications
(66 reference statements)
8
56
0
Order By: Relevance
“…Surprisingly, despite developing in two different individuals, HEPC3, HEPC43, and HEPC74 are each encoded by the same antibody heavy chain variable gene segment, V H 1-69 (Table 1). Of note, mAb AR3C, which was isolated from a subject with chronic HCV infection, also uses V H 1-69 (17), as do some other anti-HCV bNAbs (12,34). Together with the epitope mapping data, these results suggest that V H 1-69 encodes antibodies with capacity to form a public B cell clonotype that favors binding to an immunodominant broadly neutralizing HEPC3/AR3C epitope.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Surprisingly, despite developing in two different individuals, HEPC3, HEPC43, and HEPC74 are each encoded by the same antibody heavy chain variable gene segment, V H 1-69 (Table 1). Of note, mAb AR3C, which was isolated from a subject with chronic HCV infection, also uses V H 1-69 (17), as do some other anti-HCV bNAbs (12,34). Together with the epitope mapping data, these results suggest that V H 1-69 encodes antibodies with capacity to form a public B cell clonotype that favors binding to an immunodominant broadly neutralizing HEPC3/AR3C epitope.…”
Section: Resultsmentioning
confidence: 90%
“…Multiple studies have now confirmed that several anti-HCV bNAbs are encoded by the V H 1-69 antibody gene segment (12,34). This study shows for the first time to our knowledge that V H 1-69 commonly encodes a public B cell clonotype that can lead to bNAb development after a relatively brief period of infection, producing an antibody with recognition of an entire autologous viral quasispecies, thus providing what we believe to be the first potential mechanistic link between this B cell clonotype and spontaneous clearance of HCV.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The designed substitution H445P, which was generated to preferentially adopt the bnAb-bound form in a portion of E2 antigenic domain D that exhibits structural variability (31), showed the greatest level of success, both with regard to improvements in serum binding to homologous and heterologous HCVpp, as well as HCVpp neutralization of heterologous HCVpp. This design lies within a supersite of E2 associated with many broadly neutralizing antibodies (5,6,44,45), and through biophysical characterization and molecular dynamics simulation experiments, others have found that this region is likely quite flexible (27,46), providing a rationale for stabilizing key residues to engage and elicit bNAbs. Interestingly, a residue adjacent to the site of this design appears to be functionally important, with the Q444R substitution restoring viral infectivity in the context of an HCVpp with a domain E "glycan shift" substitution, N417S (8).…”
Section: Discussionmentioning
confidence: 99%
“…3e). This experiment was conducted for a further four mAbs; (i) AR4A, which targets an epitope composed of both E1 and E2 residues, (ii) AT-12009 (CD81-bs), (iii) HC84.26 (domain D) and (iv) IgH505, which targets a discontinuous epitope in E1 (residues 313-327) (32,(39)(40)(41). We saw no significant difference in the infectivities of the panel against all 4 mAbs irrespective of the cell line of production ( Fig.…”
Section: Production In Cd81 Knock-out 293t Cells Does Not Alter Hcvppmentioning
confidence: 99%